2015
DOI: 10.4238/2015.april.28.10
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between p53 and epidermal growth factor receptor expression in breast cancer classification

Abstract: ABSTRACT. This study aimed to explore new opportunities for developing targeted therapy for triple-negative breast cancer (TNBC) by analyzing the significance and association between p53 and epidermal growth factor receptor (EGFR) expression in different molecular subtypes of breast cancer. The clinical and pathological data of 264 patients with breast cancer receiving surgery in our hospital from January 2012 to August 2013 were retrospectively analyzed. According to the expression of estrogen receptor, proge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
3
10
0
Order By: Relevance
“…A study by Wang XZ et al [17] can be used as an illustration that less recognized tumor growth mechanisms have been proposed in triple-negative breast cancer patients. They have analyzed 264 patients with breast cancer divided into four molecular types plus the expression of p53 and EGFR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Wang XZ et al [17] can be used as an illustration that less recognized tumor growth mechanisms have been proposed in triple-negative breast cancer patients. They have analyzed 264 patients with breast cancer divided into four molecular types plus the expression of p53 and EGFR.…”
Section: Discussionmentioning
confidence: 99%
“…Triple-negative and HER2 overexpressed cancers were found to be larger and with higher Ki-67 as compared with the Luminal types. Beside that, triple-negative tumors showed less positive lymph nodes and higher CK5/6 and EGFR expression than the other three types, while p53 expression positively correlated with the EGFR expression only among triple-negative tumors, suggesting that tumor growth mechanism in triple-negative might differ from other breast cancers [17]. …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CK5 has been proposed by some authors to be a marker that determines basal-like features of breast cancer, along with ER, PR, HER2, and EGFR [ 86 ]. Several of the most important markers with prognostic and therapeutic values in breast cancer are summarized in Table 1 [ 87 88 89 90 91 92 93 94 95 96 97 98 99 100 101 102 103 104 105 106 107 108 109 110 111 112 113 114 115 116 117 118 119 120 121 122 123 124 125 126 127 128 129 130 131 132 133 134 135 136 137 138 139 140 141 142 ].…”
Section: Controversial Markers Of Normal Breast Tissue With Potentialmentioning
confidence: 99%
“…Sometimes, even varied molecular biological features and outcomes can be found in one of the breast cancer molecular subtypes. 17 In addition, due to the invisible and not noticeable early symptoms of breast cancer, early screening is needed to retard deterioration of breast cancer to some extent. In this present research, we combined several indices (ER, PR, HER2 and Ki-67) for better judge the prognosis of breast cancer, and the corresponding conclusion suggested that the joint detection of multiple indicators is helpful for judging the prognosis of breast cancer.…”
Section: Discussionmentioning
confidence: 99%